Assessing caregiving experience in COPD: content validity of the Zarit Burden Interview - Cruz, Joana (2018)
Caring for a relative with COPD influences multiple dimensions of carers' lives. Several instruments have been used to assess the caregiving experience in COPD,1 e.g. the Zarit Burden Interview (ZBI). This instrument was originally developed for use in carers of people with dementia, however, its applicability in COPD has not been tested. This study explored the content validity of the ZBI in carers of patients with COPD. Ten carers (68.2±6.9yrs, all female) of patients with COPD (74.7±5.3yrs, all male, FEV1=49.2±19.0%pred) participated in cognitive debriefing interviews. They were asked to complete the ZBI and verbalise their thinking process to assess the adequacy of its content and instructions. Interviews were recorded and transcribed for further analysis using the qualitative data analysis software (WebQDA). Responses to the ZBI were also analysed to explore floor/ceiling effects. From the 22 items of the ZBI, 6 items were relevant for all carers and 11 items were not relevant for at least one participant. Five of these 11 items were not relevant for ≥40% of the sample and were related to stress for providing care, embarrassment about patient’s behaviour and impacts on social/leisure time. The remaining 5 items were not consensual. Overall, the ZBI was well-understood although 8 items were less clear for some carers. They suggested: improving questions (n=1) and scoring (n=5); eliminating item 4 (n=2); including 2 questions about the caregiving context (n=1). Responses were mostly distributed in the option ‘Never/Not at all’. The ZBI in its current form should not be used to assess carer experience among those caring for patients with COPD. 1Cruz, J et al. Resp Med 2017;128:13-27